1979
DOI: 10.1111/j.1476-5381.1979.tb13690.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Pharmacokinetics, Cholinesterase Inhibition and Facilitation of Twitch Tension of the Quaternary Ammonium Anticholinesterase Drugs, Neostigmine, Pyridostigmine, Edrophonium and 3‐hydroxyphenyltrimethylammonium

Abstract: 1 The relationship between the concentration of drug in plasma, the inhibition of erythrocyte acetylcholinesterase and the facilitation of neuromuscular transmission has been studied in the rat after the administration of neostigmine, pyridostigmine, edrophonium and 3-hydroxyphenyltrimethylammonium (3-OH PTMA). 2 After the administration of neostigmine or pyridostigmine, acetylcholinesterase activity recovered only slowly due to the covalent nature of the inhibition. In contrast, recovery from the reversible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…1 -3 In priming studies of non-depolarizing muscle relaxants, increasing the size of the priming dose resulted in increasing fade of the TOF ratio, as well as an acceleration of the onset of paralysis following the administration of the second dose) 8'~9 This observation is consistent with a larger"margin of safety" at the neuromuscular junction.2~ In this study, increasing the size of the priming dose of edrophonium from 0.05 mg-kg-i to 0.30 mg,kg -1 resulted in stepwise increase (p < 0.05) in recovery of T 1 and TOF ratio with each increase in the dose up to 0.2 mg-kg-'. This effect is also consistent with the margin of safety in the inhibition of the acetylcholinesterase enzyme, as described by Barber et al 21 However, no further improvement in the recovery TI and TOF was observed with higher doses of edrophonium (0.25 and 0.3 mg'kg-I).…”
Section: Discussionsupporting
confidence: 90%
“…1 -3 In priming studies of non-depolarizing muscle relaxants, increasing the size of the priming dose resulted in increasing fade of the TOF ratio, as well as an acceleration of the onset of paralysis following the administration of the second dose) 8'~9 This observation is consistent with a larger"margin of safety" at the neuromuscular junction.2~ In this study, increasing the size of the priming dose of edrophonium from 0.05 mg-kg-i to 0.30 mg,kg -1 resulted in stepwise increase (p < 0.05) in recovery of T 1 and TOF ratio with each increase in the dose up to 0.2 mg-kg-'. This effect is also consistent with the margin of safety in the inhibition of the acetylcholinesterase enzyme, as described by Barber et al 21 However, no further improvement in the recovery TI and TOF was observed with higher doses of edrophonium (0.25 and 0.3 mg'kg-I).…”
Section: Discussionsupporting
confidence: 90%
“…Neostigmine has two binding sites with an acetylcholinesterase molecule: quaternary ammonium of the neostigmine molecule binds with the negatively charged anionic site of the enzyme and the opposite end of neostigmine creates a covalent binding with the esteratic site of the enzyme (57). This binding is stable and results in slow hydrolysis of neostigmine during which period ACh concentration remains elevated.…”
Section: Basic Pharmacology Of Reversalmentioning
confidence: 99%
“…As anticholinesterases have indirect mode of action and increase the concentration of ACh only to a relative maximum, they cannot reverse a profound NMB induced by a high or sustained concentration of muscle relaxants (44,59,(71)(72)(73)(74). Anticholinesterases have to inhibit more than 80% of the cholin esterase enzymes before their effect can be documented (57), and a ceiling effect takes place at muscle relaxant concentrations close to those required for surgical relaxation during clinical anesthesia (75,76). Thus, it is even expected that the use of any anticholinesterase is associated with residual curarization relatively frequently even when intermediate-acting muscle relaxants are used (46,(76)(77)(78)(79)(80).…”
Section: Clinical Effects Of Anticholinesterasesmentioning
confidence: 99%
“…Pharmacokinetics and metabolism of these compounds as individuals have been studied in humans and in animals (Somani et al 1972;Cohan et al 1976;Bloomquist and Thorsell 1977;Chan and Calvey 1978;Barber et al 1979;Aquilonius et al 1980;Anadon et al 1991;Taylor et al 1991;Selim et al 1995;Schoenig et al 1996). PB is metabolized mainly through hydrolysis to N-methyl-3-hydroxypyridinium following administration in rats and humans (Birtley et al 1966;Taylor et al 1991;Abu-Qare and AbouDonia 2000), while metabolism of DEET involves initial oxidative N-deethylation, ring hydroxylation, hydrolysis, and conjugation (Taylor 1986;Taylor et al 1994;Constantino and Iley 1999).…”
Section: Introductionmentioning
confidence: 97%